Reverse leaching of magnesium from ferronickel slag using alkali solvent NaOH - Prasetyo, Agus Budi; Darmawansyah, Rahadian; Mayangsari, Wahyu; Febriana, Eni; Permana, Sulaksana; Maksum, Ahmad; Oediyani, Soesaptri; Firdiyono, Florentinus; Soedarsono, Johny Wahyuadi (Eastern-European Journal of Enterprise Technologies, 2020)
A research based on magnesium extraction of ferronickel slag waste processed by reverse leaching using sodium hydroxide (NaOH) solutions has been carried out. The ferronickel slag has the main compositions of magnesium silicate and iron silicate. The early procedure of the research was the preparation of ferronickel slag grinding using a ball mill until it gets a size of –200 mesh. Secondly, the calcination of ferronickel slags to remove crystal water and increase the size of the porosity so that it would facilitate the leaching process. The next procedure was reverse leaching using sodium hydroxide (NaOH) to dissolve silica. By dissolving the silica, it was expected that the contents of elements such as magnesium and iron would increase in the residue. The variations in this ferronickel slag leaching research were leaching time, solvent concentration and leaching temperature. The reverse leaching of ferronickel slag was carried out with a time variation of 15 to 240 minutes, the temperature of 30 °C, 70 °C, and 100 °C and NaOH concentrations are 9 M, 10 M, and 11 M. The XRD (X-ray diffraction) analysis, (XRF X-ray fluorescence) analysis, SEM (Scanning Electron Microscope) analysis, and ICP-OES (Inductively Coupled Plasma) analysis were used to observe the initial characteristics of the ferronickel slag and the results after the leaching process. The characterization result towards ferronickel slag samples by XRD analysis shows that the compositions of the dominant compounds are forsterite (Mg2SiO4), enstatite (MgSiO3) and fayalite (Fe2SiO4). Moreover, the result is also supported by XRF analysis and SEM mapping analysis. The quantitative analysis of XRF shows that ferronickel slag contains 45.69 % of SiO2, 29.32 % of MgO and 16.5 % of Fe2O3. The results of the SEM mapping analysis show that Mg, Si, Fe and O bond together that indicates the presence of magnesium silicate and iron silicate. The highest percentage of magnesium extraction is 73.10 % under experimental temperature conditions of 100 °C for 240 minutes, 10 M of solvent concentration and 300 rpm of stirring speed. Increasing percentage of magnesium extraction is caused by the dissolution of silica in the leaching process. The dissolution of silica is proved by the existence of magnesium hydroxide and iron(II) hydroxide in the residue that is shown by the XRD analysis. It resulted in the MgO content in the residue increase significantly to 42.8 % as shown by the XRF analysis. Moreover, the SEM mapping analysis shows that Mg and O bond together that indicated the presence of MgO. It also can be determined that MgO is dominant